2015
DOI: 10.1016/j.phytochem.2014.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic phytocystatin expression increases nodule numbers and influences the responses of soybean (Glycine max) to nitrogen deficiency

Abstract: Keywords:Cystatin Cysteine protease Lateral root density Leaf senescence Nitrogen deficiency Nodulation Vacuolar processing enzymes abstract Cysteine proteases and cystatins have many functions that remain poorly characterised, particularly in crop plants. We therefore investigated the responses of these proteins to nitrogen deficiency in wild-type soy-beans and in two independent transgenic soybean lines (OCI-1 and OCI-2) that express the rice cystatin, oryzacystatin-I (OCI). Plants were grown for four weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Significant benefits come through joint projects on important model plants, such as Arabidopsis, tobacco and poplar, in which the consequences of genetic modification can be tested and the effects of specific gene targets characterized. Such activities result in an increased number and quality of research outputs ( Kunert et al, 2016 ; Quain et al, 2015 ). For example, in total, Professors Kunert and Foyer have published 36 joint peer-reviewed articles in International Journals together.…”
Section: Contributors To a Successful Partnershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant benefits come through joint projects on important model plants, such as Arabidopsis, tobacco and poplar, in which the consequences of genetic modification can be tested and the effects of specific gene targets characterized. Such activities result in an increased number and quality of research outputs ( Kunert et al, 2016 ; Quain et al, 2015 ). For example, in total, Professors Kunert and Foyer have published 36 joint peer-reviewed articles in International Journals together.…”
Section: Contributors To a Successful Partnershipmentioning
confidence: 99%
“…Moreover, the associated technologies that were applied in these studies were successfully transferred from Southern Africa to the rest of Africa allowing rapid development in several African partnerships. This partnership also produced improved model and crop plants that have improved tolerance to environmental stresses such as drought and low temperatures ( Kunert et al, 2016 ; Le Roux et al, 2019 ; Quain et al, 2015 ). The development and application of the biotechnological tools for plant improvement against environmental stress has become the major focus of many joint funding applications by scientists worldwide in collaboration with African partners.…”
Section: Contributors To a Successful Partnershipmentioning
confidence: 99%
“…Previous studies showed that cystatins could regulate nodulation and nodule development (Quain et al, 2015) and may play a role in regulating proteolysis in the process of nodules senescence and programmed cell death (van Wyk et al, 2014). However, which soybean cystatins play roles in nodulation, nodule development, and senescence is still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the inhibitory activities of these cystatins were analyzed and seven of them were actively transcribed in nodules (van Wyk et al, 2014). Ectopic expression of rice phytocystatin positively regulates nodulation and nitrogen deficiency of soybean (Quain et al, 2015). However, almost all of these studies were focused on individual cystatin members.…”
Section: Introductionmentioning
confidence: 99%
“…Transgenic tobacco lines ( Nicotiana tabacum ) constitutively expressing OCI showed enhanced tolerance to dark chilling (Van der Vyver et al, ), as well as an increased accumulation of RuBisCo compared to the wild type (Prins et al, ). OCI expression in soybean increased nodule numbers and delayed leaf senescence, as well as leading to a significant increase in drought tolerance (Quain, Makgopa, Cooper, Kunert, & Foyer, ). Phytocystatin expression also prevented stress‐induced programmed cell death in soybean (Solomon, Belenghi, Delledonne, Menachem, & Levine, ).…”
Section: Introductionmentioning
confidence: 99%